Surgical management of recurrent oral manifestation of Langerhans Cell Histiocytosis: case report - Santana, Nayara Conceição Marcos; Schmitz, João Ayres; Lacerda, Renata de Caralho; Lacerda, Henrique de Carvalho; Amaral, Sérgio Antonucci; Resende, Renata Gonçalves; Lacerda, Júlio César Tanos de (Journal of Oral Diagnosis, 2025)
Langerhans Cell Histiocytosis (LCH) is a rare disease characterized by the abnormal proliferation of Langerhans cells, which can affect several tissues, including the oral cavity. This case report details the follow-up and treatment over 10 years of multiple recurrences. A 21-year-old female patient presented with tooth mobility and an osteolytic lesion in the mandible, diagnosed by incisional biopsy as LCH. Initially treated with surgical excision, the patient experienced a recurrence within less than a year and was subsequently managed conservatively with intralesional corticosteroid injection. However, conservative treatment was unsuccessful, and the patient underwent segmental resection of the mandible followed by bone fixation using plates and screws for reconstruction after a mandibular fracture. The patient later developed additional recurrences in other regions of the oral cavity, requiring further surgical interventions, along with systemic manifestations, which required chemotherapy for management. This case report shows the complexity of treatment and the importance of monitoring individuals with LCH by a multidisciplinary team.